2016
DOI: 10.1038/srep23732
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a small-molecule binder of the oncoprotein gankyrin that modulates gankyrin activity in the cell

Abstract: Gankyrin is an ankyrin-repeat oncoprotein whose overexpression has been implicated in the development of many cancer types. Elevated gankyrin levels are linked to aberrant cellular events including enhanced degradation of tumour suppressor protein p53, and inhibition of gankyrin activity has therefore been identified as an attractive anticancer strategy. Gankyrin interacts with several partner proteins, and a number of these protein-protein interactions (PPIs) are of relevance to cancer. Thus, molecules that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Small molecule inhibitors and synthetic proteins inhibiting Gankyrin and restoring p53 levels in cells have been discovered and are possible candidates for further development. 120,121 A small molecule inhibitor called cjoc42 was shown to bind to the protein-protein interaction surface of PSMD10, preventing its interaction with 19S proteasome component ATPase S6 (PSMC4). 120 This blocked interaction leads to stabilization of wild-type p53 protein in osteosarcoma cells overexpressing PSMD10, when these cells are treated with cjoc42, probably because of interference with the delivery of p53 to proteasome for degradation.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Small molecule inhibitors and synthetic proteins inhibiting Gankyrin and restoring p53 levels in cells have been discovered and are possible candidates for further development. 120,121 A small molecule inhibitor called cjoc42 was shown to bind to the protein-protein interaction surface of PSMD10, preventing its interaction with 19S proteasome component ATPase S6 (PSMC4). 120 This blocked interaction leads to stabilization of wild-type p53 protein in osteosarcoma cells overexpressing PSMD10, when these cells are treated with cjoc42, probably because of interference with the delivery of p53 to proteasome for degradation.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…120,121 A small molecule inhibitor called cjoc42 was shown to bind to the protein-protein interaction surface of PSMD10, preventing its interaction with 19S proteasome component ATPase S6 (PSMC4). 120 This blocked interaction leads to stabilization of wild-type p53 protein in osteosarcoma cells overexpressing PSMD10, when these cells are treated with cjoc42, probably because of interference with the delivery of p53 to proteasome for degradation. A synthetic artificial protein is an alternative for blockade of the large PSMD10 protein-protein interaction surface, if it can be successfully delivered to cells in vivo.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…We have reported that translational activity of CUGBP1 is involved in repression of p53 and p21 genes during diethylnitrosamine (DEN)-mediated cancer (16,24), suggesting that CUGBP1 promotes liver cancer through its translational activity. We also found that phosphorylation of CUGBP1 at Ser302 is changed after DEN treatments (25). To test the role of translational activity of CUGBP1 in cancer, we generated CUGBP1-S302A knock-in mice.…”
Section: Resultsmentioning
confidence: 99%
“…ChIP studies showed that the CUGBP1-dependent C/EBP␤-HDAC1 complexes occupy the Gank promoter and partially repress Gank. Our work is clinically important, since a recent paper has identified a small drug (cjoc42) which inhibits activities of Gank (25). Therefore, future studies will show if the…”
Section: Discussionmentioning
confidence: 99%
“…These small molecule inhibitors have been designed based on the crystal structure of Gankyrin and the main function of this molecule was reduction or suppression of the binding ability of Gankyrin towards its partners [43]. A newly discovered small molecule named cjoc42 was introduced as the first small molecule capable of binding and inhibiting human Gankyrin [112]. Cjoc42 designed base on existence of ankyrin repeat sequence in Gankyrin that is important to protein-protein interactions.…”
Section: Inhibitory Protein-based Approachesmentioning
confidence: 99%